2019
DOI: 10.26434/chemrxiv.7543121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design of Bistable Gold@Spin-Crossover Core-Shell Nanoparticles Showing Large Electrical Responses for the Spin Switching

Abstract: A simple chemical protocol to prepare core–shell gold@spin‐crossover (Au@SCO) nanoparticles (NPs) based on the 1D spin‐crossover [Fe(Htrz)2(trz)](BF4) coordination polymer is reported. The synthesis relies on a two‐step approach consisting of a partial surface ligand substitution of the citrate‐stabilized Au NPs followed by the controlled growth of a very thin layer of the SCO polymer. As a result, colloidally stable core@shell spherical NPs with a Au core of ca. 12 nm and a thin SCO shell 4 nm thick, are obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…5000). 72 Still, these devices were quickly degraded upon thermal cycling due to the chemical instability of the nanoparticles under working conditions. To overcome this instability problem, they were protected with a silica shell, or deposited on graphene for indirect electrically sensing.…”
Section: Discussionmentioning
confidence: 99%
“…5000). 72 Still, these devices were quickly degraded upon thermal cycling due to the chemical instability of the nanoparticles under working conditions. To overcome this instability problem, they were protected with a silica shell, or deposited on graphene for indirect electrically sensing.…”
Section: Discussionmentioning
confidence: 99%
“…33 To further minimize the laser pulse energy required to photo-switch SCO NPs, a new approach based on a combination of gold and SCO NPs has been recently proposed. [34][35][36][37][38] Along this line, we have recently demonstrated that insertion of gold nanorods (AuNRs) in [Fe(Htrz) 2 trz] (BF 4 ) NPs largely reduces the optical peak power required to induce the spin-state transition in these SCO nanohybrids. 36,37 For simplicity we will hereby refer the NPs of [Fe(Htrz) 2 trz] (BF 4 ) and AuNRs embedded in [Fe(Htrz) 2 trz] (BF 4 ) as SCONP and Au@SCO, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Embedding AuNRs inside the SCONP provides a robust structure and good core/shell contact. 37,38 The high and broad optical absorption of Au@SCO in the visible range results in burgundy color and permits to excite the Au@SCO in a large spectral range. Besides an optical excitation at 770 nm, near the longitudinal SPR absorption peak of the AuNRs provides a means of selectively heating the core of the AuNRs.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Spin transition is always accompanied by multifaceted magnetic, electronic,o ptical and mechanical outputs, [25][26][27][28][29] which has created wide prospects for new switchable magnetic,e lectronic,optical materials and devices. [30][31][32] Indeed, photo-responsive SCO complexes are one of the most vibrant areas in this field. Forexample,the light induced excited spin state trapping (LIESST) effect can kinetically trap the excited HS* state at low temperatures for bistability, [33,34] but in principle the thermal activated relaxation process limits its application at high temperatures.…”
Section: Introductionmentioning
confidence: 99%